Exploring Mindfulness-Based Interventions for Managing Postpartum Depression: A Qualitative Study - HS, Sumita; Neha Negi; Sasanka Sekhar Pradan (Gayaku Publisher, 2024)
Postpartum depression (PPD) for much of the suffering of new mothers. Symptoms can present from sad affective experience, anxiety, tiredness, to complete disconnection of the child from herself. Traditional treatments include therapy and medication, but this study went a little deeper with the interest of mindfulness-based interventions to explore the subjective experiences in mother-child bonding, with mindfulness practiced mothers who experienced postpartum depression.In-depth 15 women diagnosed with PPD were selected, and interviews were conducted to determine how mindfulness influences emotional regulation, self-awareness, and mother-infant bonding. Various themes, including benefits and challenges of mindfulness in PPD recovery, are given to provide insight into its potential therapeutic role. The study concluded that the effectiveness of mindfulness in managing postpartum depression helps in enhancing emotional regulation, reducing anxiety, and increasing mother-infant bonding.